Sagging Eye Syndrome or Nemaline Rod Myopathy? Divergence Insufficiency with Levator Dehiscence as an Overlapping Symptom between Two Diagnoses - Stephanie S. L. Cheung; Larissa K. Ghadiali; Thomas H. Brannagan III; Gul Moonis; Phyllis L. Faust; Jeffrey G. Odel (Case Reports in Ophthalmological Medicine)
A 78-year-old woman complained of gradual, painless onset of horizontal binocular diplopia associated with progressive axial weakness. Physical examination revealed esotropia that was greater at distance than at near vision, bilateral levator dehiscence, and normal abducting saccadic speeds. Given the age of the patient and compatible clinical findings, the diagnosis of Sagging Eye Syndrome (SES) was made. However, further work-up with a muscle biopsy suggested Sporadic Late-Onset Nemaline Myopathy (SLONM) as the cause of her progressive muscle weakness. Although rare, external ophthalmoplegia has been described in the literature as a presenting symptom in SLONM. To elucidate the pathological mechanism for the patient’s diplopia, an MRI of the orbits was performed, which revealed findings consistent with SES. This case aims to highlight the importance of integrating clinical findings during the diagnostic process and serves as a reminder that diplopia can be a common symptom for an uncommon diagnosis.